The Relationship of Food Addiction With Other Eating Pathologies and Impulsivity: A Case-Control Study - Sönmez Güngör, Ekin; Çelebi, Cengiz; Akvardar, Yildiz (Frontiers in Psychiatry, 2021)
The concept of food addiction (FA) has become central in recent years in understanding the psychological aetiology of obesity. In this matched case-control study from Turkey, it was aimed to examine the prevalence of FA and related risk factors in four consecutive Body Mass Index (BMI) categories. The case group consisted of pre-operative bariatric surgery patients with BMI over 35.0 kg/m2 (n=40) and the control group was composed of age- and gender- matching individuals from the other categories, namely obese (n=35) , overweight (n=40) and normal weight (n=40). The Yale Food Addiction Scale (YFAS) and a standardized clinical interview using the DSM-5 substance use disorders criteria adopted for FA, the Eating Disorder Examination Questionnaire (EDEQ) and the Barratt Impulsivity Scale (BIS-11) were used as assessment instruments. It was found that FA was significantly associated with more serious eating pathologies, more frequent weight-cycling and earlier onset of dieting, higher impulsivity and higher BMI. Motor and total impulsivity scores showed a positive albeit week correlation with the severity of FA but no significant correlation with BMI, indicating a relationship between impulsivity and weight gain in some but not all individuals. The severity of FA predicted the increase in BMI. Our findings suggest that FA is associated with weight gain in a group of individuals, plausibly through impulsive overeating. Emphasis on FA and its clinical implications such as addiction-based treatments may improve outcomes in obesity and facilitate health promotion.